Emerging chemical and physical disinfection technologies of fruits and vegetables: a comprehensive review - Deng, Li-Zhen; Mujumdar, Arun S.; Pan, Zhongli; Vidyarthi, Sriram K.; Xu, Jinwen; Zielinska, Magdalena; Xiao, Hong-Wei (Critical reviews in food science and nutrition, 2020)
With a growing demand for safe, nutritious, and fresh-like produce, a number of disinfection technologies have been developed. This review comprehensively examines the working principles and applications of several emerging disinfection technologies. The chemical treatments, including chlorine dioxide, ozone, electrolyzed water, essential oils, high-pressure carbon dioxide, and organic acids, have been improved as alternatives to traditional disinfection methods to meet current safety standards. Non-thermal physical treatments, such as UV-light, pulsed light, ionizing radiation, high hydrostatic pressure, cold plasma, and high-intensity ultrasound, have shown significant advantages in improving microbial safety and maintaining the desirable quality of produce. However, using these disinfection technologies alone may not meet the requirement of food safety and high product quality. Several hurdle technologies have been developed, which achieved synergistic effects to maximize lethality against microorganisms and minimize deterioration of produce quality. The review also identifies further research opportunities for the cost-effective commercialization of these technologies.